Place de la littérature orale francophone dans l’enseignement de l’anglais aux cours secondaires béninois - KOTTIN, Assogba Evariste (My University, 2020)
The main objective of the current research work is to examine the primordial importance of the francophone oral literature, a literature which, in the 21st century is no more a myth but a celebrate literature and a full one, according to the great number of researchers who have already carried out research related to this, and writers have already shown and move on showing their fame of this literature. During the Conference of Ursula Baumgardt, Professor of universities at Inalco dedicated to Afrinalco Day–on Thursday, 29 January, 2015: “African Literature, an unsuspected wealth and a question of languages”. It has been stated: “Dynamic Literature, the corpus of the African literature written in European languages continues increasing, since it has gone from 2000 titles in 2000 up to 4000 titles in 100 2005 (let’s cite for example, the works of Ahmadou Kourouma or of Mariama Bâ). This literature is distinguished through its personal character, authors using it generally to describe their reality.” Due to its functions, chiefly the community thoughts’ edification, consolidation of man and supernatural relationships, it would be wonderful and fundamental to teach the English language through francophone oral literature in Beninese grammar schools and secondary schools. The methodology used is a series of questionnaire and interviews to teachers of French and English as a foreign language. The results reveal mainly that francophone oral literature can play a role in the teaching of English in Benin. As suggestions, it is important to note that this edification of community thoughts could mean that the use of this literature would consolidate interpersonal relationships between Beninese learners. Moreover, the relationships between the man and the supernatural shown through this literature would insure a true discipline which is scarce nowadays in Beninese secondary schools because the influence and horror of supernatural could horrify and change learners positively.
Keywords: littérature orale; francophone; surnaturel; horreur; discipline; enseignement; anglais.